Քաղաքական իրադրությունը Երևանի խանությունում և նրա շուրջ 1780-ականներին ըստ Ղուլամ Ալի խանի նամակագրության - Հակոբյան, Վահագն («Նաիրի» հրատ.)
After Nadir Shah’s assassination, a struggle for the throne started in Iran. The country had no powerful central authority, and the khanates of South Caucasus had semi-independent status in the course of almost half a century. Russia and the Ottoman Empire began to pursue an active policy for spreading their influence in the region and established ties with regional rulers. Both Russian and Ottoman authorities were aware of the importance of Yerevan khanate in the region, so they were trying to spread their influence there. The khans of Yerevan were paying taxes to Heraclius II and tried to maintain a semiindependent position, manoeuvring in their relationship with other powers and avoiding alliance against any power. После убийства Надир шаха, в Иране началась борьба за трон. В стране не было сильнoй центральной власти, и ханства Южного Кавказа почти полвека имели полунезависимый статус. В такой ситуации Россия и Османская империя начали проводить активную политику по распространению своего влияния в регионе и установили связи с региональными правителями. Сознавая важность Ереванского ханства, как российские, так и турецкие власти пытались установить там свое влияние. Ереванские ханы платили дань царю Ираклию II и пытались сохранить свой полунезависимый статус, маневрируя в отношениях с другими державами и избегая входить в союз против какой-либо державы.
Keywords: Հայոց պատմություն; Նամակագրություն